2009
DOI: 10.1002/ejoc.200800740
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (Alkylamino)nitroarenes by Oxidative Alkylamination of Nitroarenes

Abstract: The viability of the oxidative alkylamination process for the derivatization of electron‐deficient carboaromatics has been investigated. 1,3‐Dinitrobenzene, 1‐nitronaphthalene, and 1,5‐ and 1,8‐dinitronaphthalenes have shown to react with a wide range of alkylamines in the presence of an oxidant (KMnO4, AgMnO4, AgPy2MnO4) to give access to the corresponding N‐alkyl‐nitroarenamines in moderate to good yields. Nitroarenes are more reactive than azines towards alkylamines.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 6945… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
1
0
5
Order By: Relevance
“…Researchers have attempted to tackle this solubility problem by using electrochemical oxidation instead of chemical oxidation, thereby expanding the scope to other alkylamines than methylamine . We have previously found that AgPy 2 MnO 4 is a general oxidant for the oxidative alkylamination and successfully reported on the alkylamination of a variety of substrates both with primary and secondary alkylamines . The observation that in some cases KMnO 4 as well as AgPy 2 MnO 4 gave a good result for a specific alkylamine−substrate combination and that for another substrate in the same alkylamine AgPy 2 MnO 4 was superior to KMnO 4 indicated that solubility of the oxidant in the alkylamine cannot be the only factor governing the success of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to tackle this solubility problem by using electrochemical oxidation instead of chemical oxidation, thereby expanding the scope to other alkylamines than methylamine . We have previously found that AgPy 2 MnO 4 is a general oxidant for the oxidative alkylamination and successfully reported on the alkylamination of a variety of substrates both with primary and secondary alkylamines . The observation that in some cases KMnO 4 as well as AgPy 2 MnO 4 gave a good result for a specific alkylamine−substrate combination and that for another substrate in the same alkylamine AgPy 2 MnO 4 was superior to KMnO 4 indicated that solubility of the oxidant in the alkylamine cannot be the only factor governing the success of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…és a megfelelő aril-bromidot ( 130,10; 127,17; 122,01; 115,81; 109,32; 43,18; 31,28; 20,38; 18,11; 14,35 13 C NMR (126 MHz,9;130,4;127,1;122,1;115,8;110,1;51,2;33,1;26,1;25,3;18,2 13 C NMR (62,5 MHz CDCl3): δ = 151,6; 132,7; 131,1; 126,7; 123,2; 119,1; 55,8; 51,8; 46,3; 18,0 Hz; 6H) ppm. 13 C NMR (126 MHz, DMSO-d6) δ 147,0; 130,2; 127,2; 121,9; 115,7; 109,4; 51,3; 27,3; 20,9; 18,1 ; 142,7; 130,1; 128,8; 128,7; 127,2; 126,2; 122,1; 116,0; 109,3; 43,0; 33,3; 30,8; 18 13 C NMR (126 MHz,6;142,5;131,2;129,9;128,7;128,4;126,8;121,4;118,5;117,…”
Section: Ligandumok Szintéziseunclassified
“…(hexán:etil-acetát = 5:1). ; 132,3; 132,1; 132,0; 127,4; 119,1; 67,1; 52,5; 20,8; 17,9 8; 131,0; 127,4; 124,1; 122,2; 109,6; 43,4; 31,3; 20,5; 20,4; 18,0; 14,4 138,3;136,0;129,3;128,6;125,8;118,3;113,6;18,5. MS (EI 70 eV)…”
Section: N-(2-metoxifenil)-2-metilanilinunclassified
See 2 more Smart Citations